A real or a marginal trend in participatory budgets in local governments - Beata Zofia Filipiak; Marek Dylewski (e-Finanse: Financial Internet Quarterly, 2018)
The purpose of the article is analysis of participatory budgets as a tool for shaping decisions of local communities on the use of public funds. The authors ask the question of whether the current practice of using the participatory budget is actually a growing trend in local government finances or, after the initial euphoria resulting from participation, society ceased to notice the real possibilities of influencing the directions of public expenditures as an opportunity to legislate public policies implemented. It is expected that the conducted research will allow us to evaluate the participatory budget and indicate whether this tool practically acts as a stimulus for changes in the scope of tasks under public policies. The authors analyzed and evaluated the announced competitions for projects as part of the procedure for elaborating participatory budgeting for selected LGUs. Then, they carried out an in-depth analysis of the data used to assess real social participation in the process of establishing social policies.
Keywords: H70; H71; H72; 330; public finances; public policies; budget; participation